2023
DOI: 10.3390/ani13132220
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of Empathy as a Dual Mediator in the Relationship between Human–Pet Attachment and Quality of Life: A Survey Study among Adult Dog Owners

Abstract: This study investigates the impact of empathy on the relationship between human–dog attachment and human quality of life. A survey involving 263 dog owners was conducted to gather data on attachment to dogs, empathy, and human quality of life in Korea. The findings indicate significant correlations between attachment to dogs, human empathy, and quality of life. Specifically, both general attachment and concerns for animal rights/welfare demonstrate meaningful parallel double-mediation effects. However, cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…Bowlby’s attachment theory 35 , 79 states that the interaction with the primary attachment figure establishes the attachment style (secure or insecure 80 , 81 ), which becomes an internal working model and can be transferred to other close relationships later in life. 35 A secure attachment style in adults has been found to be associated with better mental health, 82 , 83 , 84 whereas insecure attachment style is associated with higher risk of depression and anxiety. 85 Studies on pet attachment have shown that attachment theory may be extended to human-animal attachment, 86 where the pet acts as an attachment figure.…”
Section: Discussionmentioning
confidence: 99%
“…Bowlby’s attachment theory 35 , 79 states that the interaction with the primary attachment figure establishes the attachment style (secure or insecure 80 , 81 ), which becomes an internal working model and can be transferred to other close relationships later in life. 35 A secure attachment style in adults has been found to be associated with better mental health, 82 , 83 , 84 whereas insecure attachment style is associated with higher risk of depression and anxiety. 85 Studies on pet attachment have shown that attachment theory may be extended to human-animal attachment, 86 where the pet acts as an attachment figure.…”
Section: Discussionmentioning
confidence: 99%